Effect of piston geometry on performance and emission characteristics of an LPG fuelled lean burn SI engine at full throttle condition. (5th January 2017) - Ravi, K.; Porpatham, E.
Highlights: Study to optimize piston squish area for LPG lean burn engine was carried out. 30% squish area piston results in improved performance at all operating conditions. Piston squish area beyond 30% causes instability in combustion towards lean limit. Lower HC emissions were obtained with 25% and 30% squish area pistons. NO emission increased with 25% and 30% compared to 35% and 40% squish area pistons. Abstract: This paper investigates the influence of piston squish area in LPG fuelled lean burn Spark Ignition (SI) engine on performance, emissions, combustion and cyclic variation at constant speed. The piston squish area is varied by 25%, 30%, 35% and 40% of total piston area. A single cylinder diesel engine is modified to operate as SI engine at a compression ratio of 10:1 at 1500 rpm. Tests are conducted at 100% throttle opening condition with different equivalence ratios under lean operation on different squish areas and results are analyzed. It is observed that the increase in squish area beyond 30% leads to instability in combustion towards lean equivalence limit. An appreciable increase in brake power and brake thermal efficiency is noticed in the equivalence ratios between 0.7 and 0.9 for 30% squish area piston. The HC emission level of 30% squish area piston is less compared to 25%, 35% and 40% squish area pistons. There is a noticeable increase in the NO emission in 30% and 25% squish area pistons compared to 35% and 40% squish area pistons. The investigations carried over suggest that 30% squish area piston is the most suitable for LPG fuelled lean burn SI engine.